Phase separation of 53BP1 determines liquid‐like behavior of DNA repair compartments. (1st July 2019) - Kilic, Sinan; Lezaja, Aleksandra; Gatti, Marco; Bianco, Eliana; Michelena, Jone; Imhof, Ralph; Altmeyer, Matthias
Abstract: The DNA damage response (DDR) generates transient repair compartments to concentrate repair proteins and activate signaling factors. The physicochemical properties of these spatially confined compartments and their function remain poorly understood. Here, we establish, based on live cell microscopy and CRISPR/Cas9‐mediated endogenous protein tagging, that 53BP1‐marked repair compartments are dynamic, show droplet‐like behavior, and undergo frequent fusion and fission events. 53BP1 assembly, but not the upstream accumulation of γH2AX and MDC1, is highly sensitive to changes in osmotic pressure, temperature, salt concentration and to disruption of hydrophobic interactions. Phase separation of 53BP1 is substantiated by optoDroplet experiments, which further allowed dissection of the 53BP1 sequence elements that cooperate for light‐induced clustering. Moreover, we found the tumor suppressor protein p53 to be enriched within 53BP1 optoDroplets, and conditions that disrupt 53BP1 phase separation impair 53BP1‐dependent induction of p53 and diminish p53 target gene expression. We thus suggest that 53BP1 phase separation integrates localized DNA damage recognition and repair factor assembly with global p53‐dependent gene activation and cell fate decisions. Synopsis: The DNA damage response effector 53BP1 forms characteristic foci at DNA breaks, which are here found to exhibit liquid droplet‐like self‐compartmentalization important for downstream activation of the p53 tumor suppressor. DNA repair compartments show liquid‐like properties with droplet fusions and fissions. Phase separation behavior is conferred by 53BP1, and uncoupled from upstream DNA damage detection and γH2AX‐MDC1 accumulation. 53BP1 assembly at break sites is abolished by changes in osmotic pressure, temperature, salt concentration, or disruption of hydrophobic interactions. 53BP1 optoDroplet experiments indicate multivalency and reveal sequence elements required for clustering. Disruption of 53BP1 phase separation impairs p53 activation and p21 induction upon DNA damage. Abstract : Self‐compartmentalization of the DNA double‐strand break response effector 53BP1 plays a key role in damage‐induced activation of p53 and its downstream targets.